A passive wireless triboelectric sensor via a surface acoustic wave resonator (SAWR). (December 2020) - Tan, Xulong; Zhou, Zhihao; Zhang, Liuqiang; Wang, Xue; Lin, Zhiwei; Yang, Renyu; Yang, Jin
Abstract: With the development of the Internet of Things (IoT), the requirement of wireless sensing operations is becoming increasingly desirable. Most of the current active wireless sensors require external power suppliers and complex active circuits, which limits their applications. A passive wireless sensor is a desired alternative. Hence, a passive wireless triboelectric sensor (PWTES) without active electronic components, a battery, or an energy harvester is proposed to meet the further demand for wireless monitoring. The key component of the PWTES is a surface acoustic wave resonator (SAWR). The sensing signal generated by the triboelectric nanogenerator (TENG) is applied to modulate the SAWR's response signal via a tuning network. A designed reader interrogates the SAWR and receives its response via the radiofrequency link, then demodulation is performed on the SAWR's response to obtain the sensing signal. Employing the designed PWTES, a wireless pressure sensor without a battery and an energy harvester is successfully demonstrated. The PWTES exhibited the wireless transmission of a sensing signal over a distance of 2 m, a sensitivity of 23.75 kHz/V within the TENG's voltage range of 0–5 V, and a measurement update rate of 12 kHz. The PWTES makes full use of the advantages of the TENG in sensing, and the properties of the SAWR in wireless communication, holding great potential for the miniaturization, integration, and continuous monitoring of wireless sensors in the era of the IoT. Graphical abstract: In the era of Internet of Things (IoT), passive wireless sensors show attractive application prospects because they offer the possibility of miniaturized, integration, and flexible, which can meet the potential demands of IoT applications. In this study, utilizing a triboelectric nanogenerator (TENG) and a surface acoustic wave resonator (SAWR), a passive wireless triboelectric sensor is developed. The SAWR's response signal can be modulated by the voltage from the TENG. The remote radio frequency (RF) reader transmits an RF excitation signal and receive the returned SAWR's response signal. In the designed RF reader, by demodulating the SAWR's response signal, the original voltage of the TENG is obtained. Image 1 Highlights: A wireless sensor without active circuits and power suppliers, based on triboelectric sensor and SAWR, was developed. The designed sensor exhibited a communication distance of over 2 m, and the fastest measurement update rate of 12 kHz. A frequency or amplitude modulation mechanism can be employed to sense signals.